Superior rejection profile during the first 24 months after heart transplantation under tacrolimus as baseline immunosuppressive regimen - Helmschrott M; Beckendorf J; Akyol C; Ruhparwar A; Schmack B; Erbel C; Gleissner CA; Akhavanpoor M; Ehlermann P; Bruckner T; Katus HA; Doesch AO (Dove Medical Press, 2014)
Matthias Helmschrott,1 Jan Beckendorf,1 Ceylan Akyol,1 Arjang Ruhparwar,2 Bastian Schmack,2 Christian Erbel,1 Christian A Gleissner,1 Mohammadreza Akhavanpoor,1 Philipp Ehlermann,1 Tom Bruckner,3 Hugo A Katus,1 Andreas O Doesch1 1Department of Cardiology, Angiology, Pneumology, University of Heidelberg, Heidelberg, Germany; 2Department of Cardiac Surgery, University of Heidelberg, Heidelberg, Germany; 3Institute for Medical Biometry and Informatics, University of Heidelberg, Heidelberg, Germany Background: The use of tacrolimus (TAC) in patients after heart transplantation (HTX) has increased over the last few years. Aim: In this retrospective study, we evaluated the effects of a TAC (conventional and extended-release TAC)-based immunosuppressive therapy regarding rejection profile in comparison to a cyclosporine A (CSA)-based regimen in patients after HTX.Methods: The data of 233 patients who underwent HTX at the Heidelberg Heart Transplantation Center from May 1998 until November 2010 were retrospectively analyzed. Primary immunosuppressive therapy was changed from a CSA (n=114) to a TAC (n=119)-based regimen in February 2006 according to center routine. Follow-up period was 2 years post-HTX. Primary endpoint was time to first biopsy-proven rejection requiring therapy. In all patients, routine follow-up at the Heidelberg Heart Transplantation Center was mandatory. Results: Multivariate risk factor analysis regarding time to first rejection episode showed no statistically significant differences regarding recipient age, donor age, recipient sex, donor sex, sex mismatch, ischemic time, and diagnosis leading to HTX between the two groups (all P= not statistically significant). Time to first biopsy-proven rejection was significantly longer in the TAC group (intention-to-treat analysis, n=233, log-rank test P<0.0001; per-protocol analysis, n=150, log-rank test P=0.0003). In patients who underwent a change of primary immunosuppression (n=49), a significantly longer time to first biopsy-proven rejection was also found in the primary TAC subgroup (log-rank test P=0.0297). Further subgroup analysis in the TAC subgroups showed no statistically significant differences in time to biopsy-proven rejection under extended-release TAC compared to conventional TAC (intention-to-treat analysis, log-rank test P=0.1736).Conclusion: Our study demonstrated that a TAC-based primary immunosuppressive therapy is superior to a CSA-based immunosuppressive regimen in patients after HTX regarding time to first biopsy-proven rejection. Keywords: extended-release tacrolimus, cyclosporine A, renal function